An Empirical Study on Factors Affecting Online Shopping Behavior and Intentions of Consumers (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Online shopping has become a recent  phenomenon in the field of electronic business  and has gained familiarity among consumers  around the world. Most of the companies  are now adopting online portals to sell their  products/services online. Though in countries  like India, the trend of online shopping took  some time to develop, but now a days, there  is a craze for online shopping both among the  younger and elderly populations. Compared  to traditional store shopping, online shopping  has received much more attention. The purpose  of this study is to determine the driving  factors affecting the online buying behavior of  consumers and to analyze the impact of these  driving factors on online buying intentions. To  meet the research objectives, multiple regression  analysis has been applied. The results of the  study revealed that in order of their impact size,  the most significant predictors of online buying  behavior are convenience, impulse buying  behavior, congruence, shopping enjoyment,  browsing enjoyment, value consciousness, price  consciousness and risk. The research provides a  novel finding of the strongest effect of impulse  buying behavior, which has not previously  been identified as a key antecedent to online  shopping.
Keywords: Online shopping behavior; consumer behavior; e-commerce; online shopping intention